Weight Status Moderates the Relationship between Package Size and Food Intake - Haire, Chrystal; Raynor, Hollie A. (Journal of the Academy of Nutrition and Dietetics, 2014)
Single-serving packages (SSPs) may assist people in reducing consumption. Because overweight/obese individuals and individuals practicing dietary restraint may be more responsive to external food cues regarding an amount of food to consume, we examined whether weight and restraint status influence the relationship between package size and consumption. It was hypothesized that SSPs would reduce intake in overweight/obese individuals and individuals practicing dietary restraint compared with standard packages (STPs). Using a 2×2×2 (unrestrained/restrained×normal weight/overweight×SSP/STP) between-subjects design, 64 participants (aged 23.7±3.3 years; 81.3% white; 46.9% female), from June to October 2011, were randomly assigned to receive 20 oz pretzels packaged in SSPs or STPs, and were instructed to eat the pretzels ad libitum for 4 days. Each condition in the design contained eight participants. Total grams consumed was determined by subtracting postconsumption from preconsumption weight of packages provided. Using an analysis of variance for total grams of pretzels consumed, there was a significant interaction (P=0.01) between package size and weight status. Overweight/obese participants in the SSP condition ate fewer grams of pretzels than overweight/obese participants in the STP condition (107.0±101.9 g vs 204.4±144.9; P<0.05). No effect of restraint was found on consumption. For overweight/obese individuals, fewer pretzels were consumed when packaged in SSPs compared with STPs. Thus, replacing STPs with SSPs may assist with reducing consumption in some overweight/obese individuals.